2000
DOI: 10.1152/jappl.2000.88.4.1192
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase inhibition attenuates the skeletal muscle VEGF mRNA response to exercise

Abstract: Vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), and transforming growth factor-beta(1) (TGF-beta(1)) mRNA increase in rat skeletal muscle in response to a single acute exercise bout. Nitric oxide (NO) is released locally by muscle vascular endothelium and muscle fibers during exercise, contributes to the blood flow response to exercise, and regulates mitochondrial respiration. We hypothesized that a reduction in NO production, via NO synthase inhibition, would demonstrate a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 46 publications
(59 reference statements)
4
66
2
Order By: Relevance
“…Cardiac capillary density and VEGF mRNA expression were markedly lower in eNOS -/-than in wild-type mice [12]. The inhibition of NOS diminished the exercise-induced increase in mRNAs for VEGF [23] and VEGFR-1 [24] and in protein levels of VEGF and VEGFR-2 [25] in rat skeletal muscles. Moreover, NOS inhibition failed to cause capillary angiogenesis induced by chronic electrical stimulation in rat skeletal muscle [11,25].…”
Section: Discussionmentioning
confidence: 89%
“…Cardiac capillary density and VEGF mRNA expression were markedly lower in eNOS -/-than in wild-type mice [12]. The inhibition of NOS diminished the exercise-induced increase in mRNAs for VEGF [23] and VEGFR-1 [24] and in protein levels of VEGF and VEGFR-2 [25] in rat skeletal muscles. Moreover, NOS inhibition failed to cause capillary angiogenesis induced by chronic electrical stimulation in rat skeletal muscle [11,25].…”
Section: Discussionmentioning
confidence: 89%
“…This suggests that the mechanisms responsible for the exercise-induced increase in bFGF mRNA may also be responsible for the ethanol-induced increase in bFGF mRNA. It has previously been demonstrated that bFGF gene expression is insensitive to hypoxia, nitric oxide (NO), or circulating angiotensin II in skeletal muscle (8,12,20,21). However, resting skeletal muscle bFGF mRNA is reduced in response to prostacyclin (8).…”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle, endurance training results in increases in oxidative enzymes and in the number of capillaries (3,13,42). Our laboratory has shown that acute exercise can increase angiogenic growth factor (VEGF, TGF-␤ 1 , and bFGF) mRNA in rat skeletal muscle (20,21,24). In the course of these investigations into the regulation of skeletal muscle angiogenic growth factor expression, an unanticipated increase in VEGF expression with the use of ethanol as a solvent for drug administration was found.…”
mentioning
confidence: 98%
“…The intensity of the exercise program was carefully matched in these two groups by V O2 max data, as described previously (43,45). Earlier studies have shown that this intensity of running significantly alters the biochemical profile of gastrocnemius muscle (16,45,53,55). The animals were killed two days after the last exercise training session to avoid the metabolic effects of the final run.…”
Section: Methodsmentioning
confidence: 99%